High-precision radiocarbon dating shows recent and rapid initial human colonization of East Polynesia - Wilmshurst, Janet M; Hunt, Terry L; Lipo, Carl P; Anderson, Atholl J (Proceedings of the National Academy of Sciences - PNAS, 2011)
The 15 archipelagos of East Polynesia, including New Zealand, Hawaii, and Rapa Nui, were the last habitable places on earth colonized by prehistoric humans. The timing and pattern of this colonization event has been poorly resolved, with chronologies varying by >1000 y, precluding understanding of cultural change and ecological impacts on these pristine ecosystems. In a meta-analysis of 1,434 radiocarbon dates from the region, reliable short-lived samples reveal that the colonization of East Polynesia occurred in two distinct phases: earliest in the Society Islands A.D. ∼1025-1120, four centuries later than previously assumed; then after 70-265 y, dispersal continued in one major pulse to all remaining islands A.D. ∼1190-1290. We show that previously supported longer chronologies have relied upon radiocarbon-dated materials with large sources of error, making them unsuitable for precise dating of recent events. Our empirically based and dramatically shortened chronology for the colonization of East Polynesia resolves longstanding paradoxes and offers a robust explanation for the remarkable uniformity of East Polynesian culture, human biology, and language. Models of human colonization, ecological change and historical linguistics for the region now require substantial revision.